2018
DOI: 10.1140/epjc/s10052-018-5589-3
|View full text |Cite
|
Sign up to set email alerts
|

Exact one-loop results for $$l_i \rightarrow l_j\gamma $$ l i → l j γ in 3-3-1 models

Abstract: We investigate the decays l i → l j γ , with l i = e, μ, τ in a general class of 3-3-1 models with heavy exotic leptons with arbitrary electric charges. We present full and exact analytical results keeping external lepton masses. As a by product, we perform numerical comparisons between exact results and approximate ones where the external lepton masses are neglected. As expected, we found that branching fractions can reach the current experimental limits if mixings and mass differences of the exotic leptons a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…where λ(x, y, z) = x 2 + y 2 +z 2 −2x y −2yz −2xz. This formula is also consistent with LoopTools and [48], where notations are changed as…”
Section: Appendix A: Pv Functions In Looptoolssupporting
confidence: 74%
See 3 more Smart Citations
“…where λ(x, y, z) = x 2 + y 2 +z 2 −2x y −2yz −2xz. This formula is also consistent with LoopTools and [48], where notations are changed as…”
Section: Appendix A: Pv Functions In Looptoolssupporting
confidence: 74%
“…The Feynman rules used in our calculations are listed in Table 1. We found them to appear commonly in many gauge extensions of the SM, for example in the models constructed from the following electroweak gauge symmetries: [48][49][50][51][52][53], where an important relation g Z γ V i j = e Q g Z V i j is valid. It results in that many compli-cated terms containing dangerous divergences in two contributions from diagrams 5 and 6 in Fig.…”
Section: Feynman Diagrams and Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is another arrangement that the model contains three left-handed lepton triplets, one quark triplet and two other quark anti-triplets. But, it was shown that the two arrangements are equivalent in the sense that they predict the same physics [47,48].…”
Section: A the Model Reviewmentioning
confidence: 99%